Conceptualising social media support for tacit knowledge sharing: physicians' perspectives and experiences. Issue 2 (4th April 2016) - Panahi, Sirous; Watson, Jason; Partridge, Helen
Abstract : Purpose: This paper aims to explore the potential contributions of social media in supporting tacit knowledge sharing, according to the physicians' perspectives and experiences. Design/methodology/approach: Adopting a qualitative survey design, 24 physicians were interviewed. Purposive and snowball sampling were used to select the participants. Thematic analysis approach was used for data analysis. Findings: The study revealed five major themes and over 20 sub-themes as potential contributions of social media to tacit knowledge flow among physicians. The themes included socialising, practising, networking, storytelling and encountering. In addition, with the help of the literature and the supporting data, the study proposed a conceptual model that explains the potential contribution of social media to tacit knowledge sharing. Research limitations/implications: The study had both theoretical (the difficulty of distinguishing tacit and explicit knowledge in practice) and practical limitations (small sample size). The study findings have implications for the healthcare industry whose clinical teams are not always physically co-located but must exchange their critical experiential and tacit knowledge. Originality/value: The study has opened up a new discussion of this area by demonstrating and conceptualising how social media tools may facilitate tacit knowledge sharing.